Impact of GDP, spending on R&D, the number of universities and scientific journals on research publications in environmental sciences in the Middle East - Sultan Ayoub Meo; Abeer A. Al Masri; Adnan Mahmood Usmani; Dost Muhammad Halepoto (International Journal of Occupational Medicine and Environmental Health, 2013)
Objectives: This study aimed to assess the impact of the Gross Domestic Product (GDP), spending on Research and Development (R&D), the number of universities and scientific journals on the published research documents, citable documents, citations per document and H-index in environmental sciences in the Middle East countries. Materials and Methods: All the 16 Middle East countries were included in the study. Information regarding the GDP, spending on R&D, the total number of universities and indexed journals was collected. Total number of research documents (papers), citable documents, citations per document and H-index in environmental sciences during the period 1996-2011 was recorded. The study used the World Bank, SCI-mago/Scopus, Web of Science, Journal Citation Reports (Thomson Reuters) as the main sources of information. Results: The mean GDP per capita of all the Middle East countries amounted to 18 125.49±5386.28 US$, spending on R&D was 0.63±0.28 US$, the number of universities equaled 36.56±11.33 and mean ISI indexed journals amounted to 8.25±3.93. The mean number of research documents published in environmental sciences in the Middle East countries during the period 1996-2011 was 2202.12±883.98; citable documents: 2156.87±865.09; citations per document: 8.74±0.73; and the H-index: 35.37±6.17. There was a positive correlation between the money spent on R&D and citations per documents (r = 0.6, p = 0.01), H-Index (r = 0.6, p = 0.01); the number of universities and a total of research documents (r = 0.65, p = 0.006), citable documents (r = 0.65, p = 0.006), H-Index (r = 0.50, p = 0.04), as well as ISI indexed journals and total research documents (r = 0.94, p = 0.0001), citable documents (r = 0.94, p = 0.0001), H-Index (r = 0.73, p = 0.001). Conclusions: The Middle East countries which spend more on R&D and which have a large number of universities and ISI indexed journals are likely to produce more significant volume of research papers in the field of environmental science.